Quality of life of patients with Parkinson's disease: a comparison between preoperative and postoperative states among those who were treated with deep brain stimulation - Lucca, Maria Eduarda Turczyn de; Maffini, Jhulia Farinha; Grassi, Mariana Guerrini; Abdala, Amanda Elias; Nisihara, Renato Mitsunori; Francisco, Alexandre Novicki; Farah, Marina; Fernandes de Oliveira Kumer, Tatiana von Hertwig (Arquivos de Neuro-Psiquiatria, 2022)
Background: Deep brain stimulation (DBS) is a well-established procedure for treating Parkinson's disease (PD). Although its mechanisms of action are still unclear, improvements in motor symptoms and reductions in medication side effects can be achieved for a significant proportion of patients, with consequent enhancement of quality of life. Objective: To investigate the impact of DBS on the quality of life of PD patients. Methods: This was a retrospective longitudinal study with collection of historical data in a neurosurgery center, from June 2019 to December 2020. The sample was obtained according to convenience, and the Parkinson's Disease Questionnaire (PDQ-39), Unified Parkinson's Disease Rating Scale (UPDRS) III and IV, Trail-Making Test and Verbal Fluency Test were used. Results: Data were collected from 17 patients (13 with subthalamic nucleus DBS and 4 with globus pallidus pars interna DBS). Significant improvement (p=0.008) on the UPDRS III was observed in comparing the preoperative without DBS with the postoperative with DBS. About 47.0% of the patients showed post-surgical improvement in QoL (p=0.29). Thirteen patients were able to complete part A of the Trail-Making Test and four of these also completed part B. Almost 60% of the patients scored sufficiently on the semantic test, whereas only 11.8% scored sufficiently on the orthographic evaluation. No association between implant site and test performance could be traced. Conclusions: Improvements in quality of life and motor function were observed in the majority of the patients enrolled. Despite the limitations of this study, DBS strongly benefits a significant proportion of PD patients when well indicated.
Keywords: Parkinson Disease; Deep Brain Stimulation; Quality of Life